Pendampingan Belajar Iqro bagi Anak Migran di PKBM KBRI Kuala Lumpur Malaysia - Choirul Umam, Ahmad Muntachob; A yun, Qurroti; Mahsun, Moch; Ihwanul Muttaqin, Ahmad; Ishari, Nurhafid (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2025)
This community service initiative intends to enhance fundamental Quran reading abilities through Iqro' education for migrant youth at the Community Learning Center (PKBM) PNF (National Islamic Education Center) located within the Indonesian Embassy in Kuala Lumpur, Malaysia. The impetus for this mentoring program arises from the inadequate literacy proficiency in hijaiyah letters among these children, who predominantly belong to Indonesian Migrant Workers (TKI) families. Employing a descriptive methodology rooted in a service learning framework, the program involves active participation from both educators and pupils throughout the educational experience. The stages of the activity consist of preliminary observation, crafting a lesson plan, conducting Iqro' instruction, and engaging in collective reflection regarding the outcomes of the initiative. Data compilation was carried out via observation, interviews, and documentation, followed by analysis using a descriptive approach coupled with the service learning perspective to illustrate the advancements in skills and transformations in the participants' religious conduct. The findings from the community service project reveal an enhancement in hijaiyah reading competencies, an increased enthusiasm for religious activities among children, and a rise in parental engagement regarding their children’s education. Furthermore, this initiative bolsters religious principles, discipline, and accountability among the participants. Therefore, the Iqro' mentoring program can act as a framework for promoting religious character and religious literacy among children within Indonesian migrant communities overseas